2014
DOI: 10.1089/jpm.2013.0412
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study To Evaluate Symptom-Oriented Selection of Antidepressants in Patients with Cancer

Abstract: Conducting antidepressant clinical trials is challenging in the oncology population. We approached but did not meet our feasibility goals. Depression and quality of life (QOL) scores improved with both mirtazapine and citalopram, but evidence-based pharmacologic treatments for depression in cancer patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The findings of this review are limited by the current state of research in the field such that only uncontrolled case‐series studies are available for the newer, commonly used first‐line antidepressants . A further limitation of the study conclusions is the inconsistency in study populations, with some studies including patients with depressive symptoms which may not meet diagnostic criteria for major depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this review are limited by the current state of research in the field such that only uncontrolled case‐series studies are available for the newer, commonly used first‐line antidepressants . A further limitation of the study conclusions is the inconsistency in study populations, with some studies including patients with depressive symptoms which may not meet diagnostic criteria for major depression.…”
Section: Discussionmentioning
confidence: 99%
“…56 The findings of this review are limited by the current state of research in the field such that only uncontrolled case-series studies are available for the newer, commonly used first-line antidepressants. 19,63 A further limitation of the study conclusions is the inconsistency in study populations, with some studies including patients with depressive symptoms which may not meet diagnostic criteria for major depression. The inclusion of studies using threshold scores on depression rating scales for study entry 36,37,47,48,53 is a confound due to the uncertainty regarding appropriate cut-off thresholds for depression in patients with cancer, whose scores may be elevated by cancer-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…One was a crossover trial [19], and nine were nonrandomised experimental studies [5,16,[20][21][22][23][24][25]. The longest duration of treatment was 6 months [20], and the shortest was 3 days [18].…”
Section: Search Resultsmentioning
confidence: 99%
“…Three non-randomised controlled trials were identified [16,23,24]. Two compared mirtazapine with other antidepressant drugs, one with imipramine and a control group [16], and the second with citalopram [24]. The last one compared mirtazapine with a non-interventional control group.…”
Section: Evidence From Non-randomised Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation